Learning Management for Children with Special Needs at Ya Bunayya Kindergarten Sambas District - Novi Cahya Dewi; Mohammad Ahmad Bani Amer (Bulletin of Pedagogical Research, 2023)
This research aims to describe learning management for children with special needs at YA Bunayya Kindergarten, Sambas Regency. Apart from that, this research also aims to determine learning planning for children with special needs at YA BUNAYYA Kindergarten, Sambas Regency, the implementation of inclusive education. The method used in this research is a descriptive research method with a qualitative approach with a case study design based on Ley Kekeh Marthan's theory. Data collection was carried out through interview techniques, observation. Observations were carried out to determine phenomena related to managing learning in the classroom starting from preliminary activities to final activities. The results of the research illustrate how learning for children with Down syndrome is carried out individually, which is adjusted to the child's level of ability and development. The documents collected function as supporting data. Keywords: Learning Management, Children Learning Management, Children Special Need